2003
DOI: 10.1016/s1074-7613(03)00301-7
|View full text |Cite
|
Sign up to set email alerts
|

IKKβ Is Required for Prevention of Apoptosis Mediated by Cell-Bound but Not by Circulating TNFα

Abstract: IkappaB kinase beta (IKKbeta) is required for NF-kappaB activation and suppression of TNFalpha-mediated liver apoptosis. To investigate how IKKbeta suppresses apoptosis, we generated hepatocyte-specific Ikkbeta knockout mice, Ikkbeta(Deltahep), which exhibit little residual NF- kappaB activity but are healthy with normal liver function. Unexpectedly, Ikkbeta(Deltahep) mice are slightly more sensitive than controls to LPS-induced liver apoptosis but are highly susceptible to liver destruction following concanav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
324
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(350 citation statements)
references
References 57 publications
21
324
5
Order By: Relevance
“…22 Adding to this controversy is the report that both JNK1 and JNK2 deficiency block concanavalin A-induced liver injury in vivo. 24 These findings suggest that the role of the JNK isoform in apoptosis is complex and depends on cell type and nature of the death stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…22 Adding to this controversy is the report that both JNK1 and JNK2 deficiency block concanavalin A-induced liver injury in vivo. 24 These findings suggest that the role of the JNK isoform in apoptosis is complex and depends on cell type and nature of the death stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…The role of JNK in inflammation has been revealed in a T cell-mediated and TNFα-dependent concanavalin A (ConA) mouse model for acute hepatitis. Induced TNFα in the liver upon ConA treatment results in the activation of JNK, NF-κB and AP-1 (Streetz et al, 2001;Maeda et al, 2003). Both JNK1-null and JNK2-null mouse livers display reduced liver damage after ConA treatment, indicating pivotal roles of JNK in hepatitis (Maeda et al, 2003;Hasselblatt et al, 2007).…”
Section: Jnks In Inflammation and Cancermentioning
confidence: 99%
“…Induced TNFα in the liver upon ConA treatment results in the activation of JNK, NF-κB and AP-1 (Streetz et al, 2001;Maeda et al, 2003). Both JNK1-null and JNK2-null mouse livers display reduced liver damage after ConA treatment, indicating pivotal roles of JNK in hepatitis (Maeda et al, 2003;Hasselblatt et al, 2007). A recent study using a conditional mouse model showed that mice with JNK1/2 deletion in the hematopoietic compartment, but not in hepatocytes, exhibit a profound reduction in hepatitis due to reduced TNFα expression (Das et al, 2009).…”
Section: Jnks In Inflammation and Cancermentioning
confidence: 99%
“…Importantly, hepatocyte-specific inactivation of IKKb reveals the ability of NF-kB to confer protection against TNF, which is dictated by its mode of signalling. Whereas mice lacking IKKb in hepatocytes are resistant to liver damage that results from administering recombinant TNFa or LPS, which induces the synthesis of soluble TNF, these mice remain sensitive to concanavalin A, which promotes hepatocyte apoptosis by triggering signalling through membrane-bound TNF (Maeda et al, 2003). The failure of LPS to induce apoptosis in IKKb-deficient hepatocytes is supported by the finding that NF-kB is still activated, albeit at reduced levels, in the IKKb-deficient cells by soluble TNF (Luedde et al, 2005).…”
Section: Ikkbmentioning
confidence: 99%
“…Despite NF-kB function in the liver having been shown to be required for hepatocyte proliferation following hepatectomy (Iimuro et al, 1998), surprisingly inhibition of NF-kB function in hepatocytes does not prevent their proliferation (Chaisson et al, 2002). Instead, experiments that involved the conditional deletion of IKKb in hepatocytes or resident hemopoietic cells of the liver such as macrophage-like Kupffer cells established that hepatocyte proliferation was only dependent on activating NF-kB in the hemopoietic compartment of the liver (Maeda et al, 2003. This finding establishes that it is the NF-kB-dependent production of TNF by non-parenchymal liver cells that promotes the growth of hepatocytes.…”
Section: Ikkbmentioning
confidence: 99%